Effect of glycemic control on albumin excretion in urine in diabetics - Shah, Pankil K.; Chauhan, Asutosh P. (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes Mellitus (DM) is commonest endocrine disorder worldwide. It is associated with variety of complications such as retinopathy, neuropathy and nephropathy. The severity of the complications depends on treatment strategies, duration of diabetes and glycemic control. Microalbuminuria (MA) is an earliest predictor of nephropathy in patients of diabetic nephropathy and Diabetic Nephropathy is most common cause for End Stage Renal Disease (ESRD) worldwide. It accounts for >40% of patients with ESRD. Methods: The present study investigated effect of glycemic control on microalbuminuria. We studied 150 diabetic patients with duration of diabetes more than 3 years. Investigations like glycated hemoglobin (HbA1C) and fasting blood glucose were carried out to evaluate glycemic control and albumin in urine to evaluate early renal involvement. Results: Out of 150 patients included in the study, 107 had poor glycemic control and 33 patients had good glycemic control. The HbA1C less than 7% is taken as cut off point for control of diabetes. The mean value of albumin in urine was 34.5 mg/L in the group of diabetics with good glycemic control and the same was 60.7 mg/L in the group of diabetics with poor glycemic control and this change was statistically significant (p<0.05). Conclusions: It is concluded that those patients with good glycemic control have decreased risk of developing microalbuminuria.